Data-Center Farming: Exploring the Potential of Industrial Symbiosis in a Subarctic Region - Cristina Ramos Cáceres; Suzanna Törnroth; Mattias Vesterlund; Andreas Johansson; Marcus Sandberg (Sustainability, 2022)
As our world becomes increasingly digitalized, data centers as operational bases for these technologies lead to a consequent increased release of excess heat into the surrounding environment. This paper studies the challenges and opportunities of industrial symbiosis between data centers’ excess heat and greenhouse farming, specifically utilizing the north of Sweden as a case study region. The region was selected in a bid to tackle the urgent urban issue of self-sufficiency in local food production. A synergetic approach towards engaging stakeholders from different sectors is presented through a mix of qualitative and quantitative methods to facilitate resilient data-center-enabled food production. The paper delivers on possible future solutions on implementing resource efficiency in subarctic regions.